First-principles study on the electronic structures and optical properties of CsVO3. (17th August 2020) - Luo, Jiaolian; Yang, Anqi; Wang, Xiaohui; Liu, Keyin
Abstract: In this paper, a CSVO3 phosphor for white LED has been successfully prepared by solid-state synthesis and has been characterized. The CsVO3 was simulated by Materials Studio software based on density functional theory (DFT). The results show that the CsVO3 sample has a direct optical transition with band gap energy of 3.143 eV. Under ultraviolet excitation in the range of 300–390 nm, the emission spectrum of CsVO3 phosphors ranges from 400 to 700 nm, and its peak emission spectrum is near 492 nm, and shows yellow color fluorescence emission. These results indicate that CsVO3 phosphor can be used as a promising white phosphor for white LED.